2017
DOI: 10.4236/health.2017.98088
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Characteristics of Thoracic Outlet Syndrome in High School Baseball Players

Abstract: Thoracic outlet syndrome (TOS) is one of the common neurovascular disorders of the upper extremities, and the compression or traction of the brachial plexus is the main pathology. We hypothesized that baseball players are more likely to be affected by TOS compared with other overhead-throwing athletes because of strenuous use of their throwing arm. The purpose of this study was to investigate the prevalence and clinical characteristics of TOS in high school baseball players. One thousand two hundred eighty-eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…One cross-sectional study of 1288 Japanese high school baseball players demonstrated a 32.8% prevalence of TOS, of which the majority was hypothesized to be nTOS. 127 This figure is three times higher than the prevalence found in industrial workers. 128 A study analyzing U.S. collegiate athlete injury data found that baseball and softball were the sports most commonly associated with nTOS, followed by swimming and water polo.…”
Section: Neurogenic Thoracic Outlet Syndromementioning
confidence: 71%
See 1 more Smart Citation
“…One cross-sectional study of 1288 Japanese high school baseball players demonstrated a 32.8% prevalence of TOS, of which the majority was hypothesized to be nTOS. 127 This figure is three times higher than the prevalence found in industrial workers. 128 A study analyzing U.S. collegiate athlete injury data found that baseball and softball were the sports most commonly associated with nTOS, followed by swimming and water polo.…”
Section: Neurogenic Thoracic Outlet Syndromementioning
confidence: 71%
“…Prevalence studies of nTOS in throwing athletes compared with the general population support the anatomical and biomechanical risk factors that throwers are at increased risk for nTOS. One cross‐sectional study of 1288 Japanese high school baseball players demonstrated a 32.8% prevalence of TOS, of which the majority was hypothesized to be nTOS 127 . This figure is three times higher than the prevalence found in industrial workers 128 .…”
Section: Peripheral Neuropathies In Throwing Athletesmentioning
confidence: 97%
“…Prevalence studies of nTOS in throwing athletes compared to the general population support the anatomical and biomechanical arguments suggesting that throwers are at increased risk for nTOS. Otoshi et al showed an incidence of symptomatic TOS in 32.8% of Japanese high school baseball players, which they hypothesized was primarily nTOS 20 . This rate of TOS is three times higher than the incidence found in industrial workers by Sallstrom et al 21 A study analyzing U.S. collegiate athlete injury data found that baseball and softball were most associated with nTOS, followed by swimming and water polo 18 …”
Section: Overhead Athlete Biomechanicsmentioning
confidence: 96%
“…As a result, compression may occur in neurovascular structures in the region. [25] Clinical features: Neurogenic TOS involve include paresthesia, numbness,, and weakness radiating from the neck region and shoulder and extending into the arm and hand. TOS can cause paresthesia in a wide area.…”
Section: Thoracic Outlet Syndrome (Tos)mentioning
confidence: 99%